2010
DOI: 10.2147/cpaa.s6262
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptors are expressed by small-cell lung cancer and are potential targets for effective treatment

Abstract: We previously showed that functional N-methyl-D-aspartate (NMDA) receptors are expressed by human neuroblastoma cells. In this study we demonstrate functional NMDAR1 and NMDAR2 receptors are expressed by small-cell lung cancer (SCLC) classical cell lines NCI H146, NCI H345, and DMS 53, by variant cell line NCI H82, and by most SCLC tumors, and that these receptors are important for the growth of human SCLC tumor xenografts in mice. Reverse transcription-polymerase chain reaction demonstrated mRNA for both rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
2
19
0
1
Order By: Relevance
“…Several studies reported that a glutamate receptor antagonist inhibits tumor growth, whereas a glutamate scavenger shows positive results in survival of animals with glioma21,22). NMDAR antagonists, such as memantine, MK-801 (dizocilpine), ifenprodil, Ro25-6981, and AP5, have an antiproliferative effect on cancer cells1,17,22,25,28). Our study also showed that memantine has an antiproliferative effect on human glioma cell lines.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Several studies reported that a glutamate receptor antagonist inhibits tumor growth, whereas a glutamate scavenger shows positive results in survival of animals with glioma21,22). NMDAR antagonists, such as memantine, MK-801 (dizocilpine), ifenprodil, Ro25-6981, and AP5, have an antiproliferative effect on cancer cells1,17,22,25,28). Our study also showed that memantine has an antiproliferative effect on human glioma cell lines.…”
Section: Discussionsupporting
confidence: 71%
“…In glioma cells, AMPAR is believed to promote cellular proliferation and survival, via activation of the PI3K/AKT pathway, EGFR expression and the MAPK pathway8,10,23). NMDAR antagonists also have the potential for inhibiting tumor proliferation1,17,22,25). Dizocilpine, an NMDAR1 antagonist, inhibits proliferation of lung cancer cell lines by inhibiting the extracellular signal-regulated kinase 1/2 pathway25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was replicated with another glycine B site antagonist (L-701,252) using the NCI-H345 cell line. The relevance of NMDAR1 receptors to tumor cell proliferation was further shown with affinity-purified polyclonal antibodies to NMDAR1, which were able to significantly reduce proliferation ( P < 0.001) at dilutions of 1:10 and 1:50 [4]. These data support the accessibility of the receptor protein on the cell surface.…”
Section: Introductionmentioning
confidence: 78%
“…Human small cell lung cancer (SCLC) tumor cell lines (i.e., NCI-H345, DMS-53, NCI-H146, and NCI-H82) were shown to express functional NMDA receptors; additionally, tissue sections of eight of 10 SCLC tumors stained positive with anti-NMDAR1 antibodies [4]. Moreover, all six of the sections of metastatic and recurrent disease stained strongly positive for expression of NMDAR1 .…”
Section: Introductionmentioning
confidence: 99%